Impact Implementation Of Psak 70 Related To Tax Amnesty On Reporting Of The Firm (Case Study On Cv Btari Senja) - Winarso, Widi; Panday, Rorim (Jurnal Manajemen Bisnis, 2018)
This study aims to test how big the impact of the application of PSAK (Statement of Financial Accounting Standards) 70 to the Financial Statement of CV Btari Senja before and after tax amnesty applied. The sampling technique used is the triangulation time technique (triangle time). The sample is determined using the credibility method. This research uses the data of CV Btari Senja Financial Report in 2015 and 2016. The results of this study stated that the application of PSAK 70 related tax amnesty greatly affect the Financial Statements at CV Btari Senja, especially in Reports of Debt and Assets.